Prior exercise training and experimental myocardial infarction: A systematic review and meta-analysis - Veiga, Eduardo Carvalho de Arruda; de Melo, Brunno Lemes; Vieira, Stella de Souza; Simões, Ricardo S.; Valenti, Vitor E. [UNESP]; Campos, Marcelo Ferraz; Do Vale, Joseane Elza Tonussi Mendez Rossetti; Rica, Roberta Lukesvicius; Soares-Júnior, José Maria; Baracat, Edmund Chada; Serra, Andrey Jorge; Baker, Julien S.; et al. (Elsevier, 2020)
Exercising prior to experimental infarction may have beneficial effects on the heart. The objective of this study was to analyze studies on animals that had exercised prior to myocardial infarction and to examine any benefits through a systematic review and meta-analysis. The databases MEDLINE, Google Scholar, and Cochrane were consulted. We analyzed articles published between January 1978 and November 2018. From a total of 858 articles, 13 manuscripts were selected in this review. When animals exercised before experimental infarction, there was a reduction in mortality, a reduction in infarct size, improvements in cardiac function, and a better molecular balance between genes and proteins that exhibit cardiac protective effects. Analyzing heart weight/body weight, we observed the following results-Mean difference 95% CI--0.02 [-0.61,0.57]. Meta-analysis of the infarct size (% of the left ventricle) revealed a statistically significant decrease in the size of the infarction in animals that exercised before myocardial infarction, in comparison with the sedentary animals-5.05 [-7.68,-2.40]. Analysis of the ejection fraction, measured by echo (%), revealed that animals that exercised before myocardial infarction exhibited higher and statistically significant measures, compared with sedentary animals 8.77 [3.87,13.66]. We conclude that exercise performed prior to experimental myocardial infarction confers cardiac benefits to animals.
Keywords: Exercise Training; Experimental Myocardial Infarctions; Meta-Analysis; Prior Exercise; Running; Swimming; Systematic Reviews